A Comparative Case Study of Electric Utility Companies’ Use of Energy Democracy in Strategic Communication - McKasy, Meaghan; Yeo, Sara K. (Frontiers in Communication, 2018)
A substantial increase in distributed renewable energy resources is changing the face of the energy environment, leading to strategic communication efforts by key stakeholders. The energy democracy movement supports this transformation from fossil fuels to distributed renewable energy and aims for equitable involvement of publics in energy decision-making. These tenets challenge utility company earnings as they are directly related to energy sales and infrastructure returns on investment (ROI). Proposals by electric utility companies to restructure net metering policies as a solution to financial issues have been criticized as prohibitive to the success of renewable energy advancement. To address these disagreements, the Edison Electric Institute and a communication firm, Maslansky & Partners, created The Future of Energy: A Working Communication Guide for Discussion. This handbook provides utility companies with strategic communication guidelines to portray themselves as supportive of renewables within a dynamic energy industry. We posit that aspects of the energy democracy movement have been employed by electric utility companies, as shown through use of the handbook, as a strategy for communicating with customers in discussions around net metering. We examine two case studies in states with recent controversial net metering policy changes by analyzing utility company websites and press releases for use of the communication handbook terminology. We found that, in both cases, the suggested language was used to position their companies as pro-renewable energy and their utility-scale projects as more equitable for their customers. Additionally, we found differences between each company’s use of key terms from the handbook. We posit this is due to the temporal context of each net metering debate at the time of the handbook release. Conclusions and future directions for research in the growing area of energy democracy are discussed.